2021
DOI: 10.1093/cdn/nzaa086
|View full text |Cite
|
Sign up to set email alerts
|

Native Hawaiian Complementary Feeding Practices as Told by Grandparents: A Transgenerational Experience

Abstract: Background Infancy is a significant disease prevention and health promotion stage in life. There is a need to examine factors influencing complementary feeding among Native Hawaiians through an indigenous framed lens. Objective To identify Hawaiian complementary feeding practices through in-depth interviews with kūpuna (grandparents) from across the state of Hawai‘i. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…As was anticipated based on current research, males (fathers) were reported to have a more prominent role in cooking and feeding activities than in previous generations [46]. However, grandparents' role in cooking and feeding was much less prevalent than is traditional for families of the NHPI population [35]. Although, the small sample size in this study is acknowledged.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…As was anticipated based on current research, males (fathers) were reported to have a more prominent role in cooking and feeding activities than in previous generations [46]. However, grandparents' role in cooking and feeding was much less prevalent than is traditional for families of the NHPI population [35]. Although, the small sample size in this study is acknowledged.…”
Section: Discussionmentioning
confidence: 57%
“…Similarly, most caregivers in both groups were receptive to the advice of HCPs relating to unadvised feeding practices, including pre-mastication. Pre-mastication is a transgenerational feeding practice, which holds cultural significance in the Native Hawaiian population [35]. This practice nourishes the infant's soul [51].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…31 In addition to educational resources available, qualitative research has underscored the importance of understanding and celebrating diverse cultures and practices regarding early feeding. 32 Scoping reviews, such as the one described by Monteith et al, 33 on qualitative literature related to Indigenous infant feeding experiences, could provide even more insights to understanding the context of culture and traditions on infant feeding practices. Continued efforts by both WIC educators and health care providers to emphasize the importance of early experiences with different food textures, using a culturally competent approach, could help support the development of positive current dietary behaviors and practices and potentially influence later dietary behaviors for WIC and non-WIC participants alike.…”
Section: Discussionmentioning
confidence: 99%